Soil and Drought Basic Processes (Taylor & Francis, 2024)
Drought, a serious global issue, is being aggravated by climate change. Both pedological and agronomic droughts are a major risk factor with adverse effects on agronomic productivity, food and nutritional security, and human wellbeing.
English
Keywords: Biology, life sciences; Biology; life sciences